Histological development of ligamentum teres and its vascularisation in the human fetuses - Jandial, Sonia (International Journal of Research in Medical Sciences, 2019)
Background: Ligamentum teres is the ligament of the hip joint. It is flat and triangular in shape. The ligamentum teres starts developing in the fetal life during 10-11 weeks. The present work was undertaken chiefly to gain insight into the pattern of sequential development of ligamentum teres and to compare the findings of other authors with the observations made in the present study and to correlate these findings clinically to find out the function of ligamentum teres. Methods: The present study was undertaken on 40 fetuses of varying gestational periods collected from the operation theatre, labour room and obstetrics wards of department of Gynaecology and Obstetrics, Government Medical College, Jammu and other areas of Jammu, 10% Formalin was used as preservative. The hip joints of both the sides were dissected carefully. 5% solution of Gooding and Stewart’s was used for decalcification. Paraffin wax embedding method was used for preparing the tissue for section cutting. Staining was done by Harri’s Hematoxylin and Eosin stain and Masson’s Trichrome stain. The slides were then examined under microscope for important findings. Results: The ligamentum teres is seen by 10½ weeks. Blood vessels appear in 12½ weeks. Ramification of blood vessels in this ligament is seen by 21½ weeks. Through this ligament, the blood vessels are seen limited up to the fovea capitis femoris by about 16½ weeks and by 18½ weeks they penetrate deep into the head of femur. Ligamentum teres is lined by thin synovial membrane at 19th week. Conclusions: The ligamentum teres develops by 10½ weeks. It arises in-situ as it develops in the same position as it occupies in the adult but as age advances, it shows much differentiation and resembles the adult features.